Morphometry of megakaryocytes in the liver of New Zealand White rabbits during intrauterine and postnatal development - Pacheco,Maria Rita (2002)
The hepatic megakaryocytic cells of New Zealand White rabbit in the intrauterine phase and in the immediate postnatal period were studied. Statistical analysis of the data concerning the cytoplasm and nucleus of those cells, i.e., area, perimeter, maximum diameter, minimum diameter, volume and shape factor, presented significant differences (p<0.01) for F values concerning the life phases studied on15th, 22nd and 29th day of intrauterine life and 10th day of postnatal life, and for F values for animal within each phase. The Tukeys test showed that most of the parameters studied in the cytoplasm and nucleus of these megakaryocytic cells presented the lowest values on the 15th day of intrauterine life and the highest on the 22nd day of the same phase.